2021
DOI: 10.15587/1729-4061.2021.237940
|View full text |Cite
|
Sign up to set email alerts
|

Justification of pectin concentrate safe storage terms by pectin mass ratio

Abstract: The problem of removing heavy and radioactive metals from the human body is relevant all over the world. Recent research has shown that it is more effective to use substances contained in natural food products, including pectin. Pectin has a favorable effect not only under acute exposure to metals, but also with their prolonged entry into the body, which is typical for an environmental load of residents of industrial regions and modern megalopolis. The use of pectin substances as natural detoxicants requires r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Paper [12] reports the results of a study of pectin substances. It has been shown that the problem of removing heavy and radioactive metals from the human body is relevant all over the world.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Paper [12] reports the results of a study of pectin substances. It has been shown that the problem of removing heavy and radioactive metals from the human body is relevant all over the world.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Freezing is accompanied by a deep decrease in the temperature of the fruit and the transformation of moisture into ice, i. e., dehydration. The formation of ice crystals causes changes in the tissue structure of the product, the degree of which depends on the freezing rate [33]. With slow freezing of fruits at relatively high temperatures, ice crystals are formed mainly in the intercellular spaces.…”
Section: Analysis Of Data In Tablementioning
confidence: 99%